Optimisation of alpha-amylase inhibitor production in solid state fermentation - Fatoki, O. A.; Onilude, A. A.; Ekanola, Y. A.; Akanbi, C. T. (Frontiers in Pharmacology, 2023)
Though not a known producer of alpha-amylase inhibitor, the potential of Streptomyces xinghaiensis AAI-2 to produce this important metabolite was assessed and the process optimised in solid substrate using response surface methodology. The isolate was grown in an inoculum medium, inoculated into wheat bran and supplemented with a basal medium for production of alpha amylase inhibitor. Optimum conditions were determined by Response Surface Methodology. The extract was recovered using sodium phosphate buffer at refrigerated temperature and assay for the presence of alpha-amylase inhibitor was carried out by Dinitrosalicylic acid method. Based on the results of the experimental trials and iteration with those values, it was predicted that optimal pH for alpha-amylase inhibitor production using S. xinghaiensis in solid culture of wheat bran was pH 6.4-6.9 while optimal moisture content and incubation time were predicted as 71-73% and 9-12 days respectively.